2020
DOI: 10.1093/treephys/tpaa023
|View full text |Cite
|
Sign up to set email alerts
|

Embryo transcriptome and miRNA analyses reveal the regulatory network of seed dormancy in Ginkgo biloba

Abstract: Seed dormancy is crucial for plant survival and prevents seed germination out of season. However, little is known about the regulatory mechanism of morphophysiological seed dormancy. Ginkgo biloba L. is one of the most ancient gymnosperms, and the completion of seed germination in this species requires cold and moist stratification. Here, we observed that at the mature seed stage, the embryo was not fully developed in G. biloba seeds. During dormancy stages, the length and weight of the embryo significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…In addition, the absolute ABA content was much higher than the absolute GA3 content and the ABA/GA3 ratio showed a similar trend to ABA content (Figure 1B-E). These findings are consistent with those in the seeds of red bayberry [29], celery [30], and ginkgo [31]. Simultaneously, the expression patterns of several ABA and GA biosynthesis and deactivation genes, including SDRs, CYP707As, KO, KAO, and GA20oxs, exhibited high correlations with the changes in ABA and GA3 levels (Figure 4A).…”
Section: Metabolism and Regulation Of Plant Hormones In Callery Pear ...supporting
confidence: 86%
“…In addition, the absolute ABA content was much higher than the absolute GA3 content and the ABA/GA3 ratio showed a similar trend to ABA content (Figure 1B-E). These findings are consistent with those in the seeds of red bayberry [29], celery [30], and ginkgo [31]. Simultaneously, the expression patterns of several ABA and GA biosynthesis and deactivation genes, including SDRs, CYP707As, KO, KAO, and GA20oxs, exhibited high correlations with the changes in ABA and GA3 levels (Figure 4A).…”
Section: Metabolism and Regulation Of Plant Hormones In Callery Pear ...supporting
confidence: 86%
“…Dynamic variations of the ABA/GA ratio during germination showed that DXWR had a similar ratio with 9311 during 24 h imbibition, but significantly higher ratio than 9311 during 24 h-48 h imbibition (Fig. 2), consistent with previous studies showed that a high ABA/GA ratio is critical for the induction of maturation and germination suppression in early seed development programming [25]. In our results, the ABA/IAA ratio for DXWR only slightly fluctuated, but one ratio slack at 36 h and two ratio peaks at early and late stages of seed germination for 9311 were observed (Fig.…”
Section: The Levels Of Endogenous Hormones In Wild Ricesupporting
confidence: 90%
“…Xiao et al found that the content of IAA in the embryo gradually increased during seed germination, and then reach a maximum at 12 h, but then decreased at 48h [24]. Jia et al found that GA biosynthesis and signaling transduction specifically act on seed dormancy release [25]. Several physiological and genetic analyses have demonstrated the requirement of GA for germination; GA can promote seed germination through enhancing the growth potential of the embryo and overcoming the mechanical barriers imposed by covering layers surrounding embryo [4,12].…”
Section: The Levels Of Endogenous Hormones In Wild Ricementioning
confidence: 99%
“…Ginkgo biloba L., a fascinating and economically important gymnosperm, is the only living representative of the order Ginkgoales, which probably originated circa 280 million years ago [12]. It exhibits some unique features related to its sexual reproduction process, phylogenetic position, and evolutionary history [13][14][15]. At present, G. biloba has a wide Forests 2021, 12, 1255 2 of 16 distribution across different elevations and latitudes and generally has a long lifespan.…”
Section: Introductionmentioning
confidence: 99%